Genetic differentiation, speciation, and phylogeography of cactus flies (Diptera: Neriidae: Odontoloxozus) from Mexico and south‐western USA. (12th July 2013) - Pfeiler, Edward; Richmond, Maxi Polihronakis; Riesgo‐Escovar, Juan R.; Tellez‐Garcia, Aldo A.; Johnson, Sarah; Markow, Therese A.
Abstract : Nucleotide sequences from the mitochondrial cytochrome c oxidase subunit I (COI) gene, comprising the standard barcode segment, were used to examine genetic differentiation, systematics, and population structure of cactus flies (Diptera: Neriidae: O dontoloxozus ) from Mexico and south‐western USA. Phylogenetic analyses revealed that samples of O dontoloxozus partitioned into two distinct clusters: one comprising the widely distributed O dontoloxozus longicornis (Coquillett) and the other comprising O dontoloxozus   pachycericola Mangan & Baldwin, a recently described species from the Cape Region of the Baja California peninsula, which we show is distributed northward to southern California, USA. A mean Kimura two‐parameter genetic distance of 2.8% between O . longicornis and O. pachycericola, and eight diagnostic nucleotide substitutions in the COI gene segment, are consistent with a species‐level separation, thus providing the first independent molecular support for recognizing O. pachycericola as a distinct species. We also show that the only external morphological character considered to separate adults of the two species (number of anepisternal bristles) varies with body size and is therefore uninformative for making species assignments. Analysis of molecular variance indicated significant structure among populations of O . longicornis from three main geographical areas, (1) Arizona, USA and Sonora, Mexico; (2) Santa Catalina Island, California, USA; and (3) central Mexico (Querétaro and Guanajuato), although widely‐separated populations from Arizona and Sonora showed no evidence of structure. A TCS haplotype network showed no shared haplotypes of O . longicornis among the three main regions. The potential roles of vicariance and isolation‐by‐distance in restricting gene flow and promoting genetic differentiation and speciation in O dontoloxozus are discussed. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 245–256.